Salah rules - Mugford , Simon; Green , Dan (London Welbeck, 2022)
Read all about the rise of mo salah as he went from playing street football with his mates to winning trophies with liverpool and become a global sports icon
Famous people
Keywords: Biographies; Great Britain; Soccer players